Analysing delay causes and effects in Ghanaian state housing construction projects. Issue 1 (5th January 2015) - Rolf A. Lundin; Dr Kjell Tryggestad, Professor; Amoatey, Charles Teye; Ameyaw, Yaa Asabea; Adaku, Ebenezer; Famiyeh, Samuel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess the causes and effects of delays in public sector housing projects in Ghana. Design/methodology/approach – A purposive sampling approach was used in selecting the respondents for the study. These were experts working on various state housing construction projects in Ghana. Findings – Results from the study showed that the critical factors that contribute to project delays in Ghana are; delay in payment to contractor/supplier, inflation/price fluctuation, price increases in materials, inadequate funds from sponsors/clients, variation orders and poor financial/capital market. The critical effects of delays are cost overrun, time overrun, litigation, lack of continuity by client and arbitration. Research limitations/implications – This paper is limited to causes and effects of project delays in Ghana based on data collected from only one state institution. Due to geographic constraints the researchers were unable to sample state institutions across Ghana involved in various housing projects. Practical implications – This paper has documented the critical state housing construction project delay factors in Ghana. The results will help project managers and policymakers appreciate the effects of these delays on project outcomes. Social implications – Measures aimed at reducing cost of housing projects in Ghana can translate into significant benefits to the poor and support achievement of government objective of providing affordable housing to low income citizens. Originality/value – This research focussed on the key factors and best practices that lead to the success of state housing projects within the Ghanaian context.